Vertical Jump to Female and Male Basketball Players in Albania - Shytaj, Orest (European Journal of Multidisciplinary Studies, 2021)
Vertical jump is one of the basic elements in collective sports such as volleyball, basketball, football, etc. The reason of this study is the evaluation of this element and other parameters of the Albanian National Championship basketball players female and male. From the specificity of their training, there are differences in the physical qualities of individual performance, where one of the elements is vertical jumping. The performance profiling of basketball players is important to distinguish the anthropometric and physical characteristics from other sports. Basketball players were tested in different periods before and after the training with their coaches. Subjects were 59 Female (F) mean age 18.1 years old and 60 Male (M) mean age 18.8 years old. They evaluated us; Body Height (BH), Body Mass (BMI %), Body Weight (BW), Squat Jump (SJ), Countermovement Jump (CMJ) and Drop Jump 40cm (DJ). From the obtained data of the test was observed even the effect of the training that these athletes have done for the jumping level, assessment of explosive strength and maximum power. Differences were seen to individual basketball players between two periods, before and after the testing. The evaluation of these tests is one of the key features of a vertical jump as one of the specific technical element in the game on air in the sport of basketball. The obtained results suggest changes in sporting performance of “vertical jump” in the force settings, speed and power.